2011
DOI: 10.3892/ol.2011.327
|View full text |Cite
|
Sign up to set email alerts
|

Anal function-preserving subtotal intersphincteric resection/partial external sphincteric resection with hybrid 2-port hand-assisted laparoscopic surgery (Mukai's operation) for very low stage I rectal cancer: A case report

Abstract: Abstract.A 62-year-old male patient underwent endoscopic mucosal resection (EMR). Additional hybrid 2-port handassisted laparoscopic surgery (HALS) (Mukai's operation) was performed for early rectal cancer located at the distal border of the rectum/below the peritoneal reflection (Rb) region [SM massive invasion/ly+/vertical margin (VM)X] via a small transverse incision, approximately 55 mm long, at the superior border of the pubic bone. After the pelvic floor muscles were dissected by laparoscopy-assisted man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The results of our multiple studies showed that both short-term and long-term outcomes were comparable between HALS and CL (13,14). In addition, we reported other advantages of HALS, including minimum surgical invasiveness due to small incision, decreased incidence of operative site infection, shorter postoperative hospital stay period, and surgical technique with 2-3 ports, as well as medical costs (13)(14)(15)(16)(17). This time, we also investigate the causes of death.…”
Section: Discussionmentioning
confidence: 78%
“…The results of our multiple studies showed that both short-term and long-term outcomes were comparable between HALS and CL (13,14). In addition, we reported other advantages of HALS, including minimum surgical invasiveness due to small incision, decreased incidence of operative site infection, shorter postoperative hospital stay period, and surgical technique with 2-3 ports, as well as medical costs (13)(14)(15)(16)(17). This time, we also investigate the causes of death.…”
Section: Discussionmentioning
confidence: 78%
“…But the remarkable magnified view provided by the monitor of laparoscopic operation system has become more advantageous and fascinating and enables safe and accurate manipulation at sites such as the deep pelvic floor, lower bladder, posterior surface of the prostate and anal region, where visualization is difficult to achieve during open surgery and manipulation is usually carried out under nearly blind conditions [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the scar on the abdomen caused by this procedure may cause dissatisfaction in some patients. In recent years, some researchers have reported transanal specimen extraction in laparoscopic anterior rectal resection [6][7][8], including intersphincteric resection (ISR) [9][10][11], and rectal eversion-resection [12,13]. However these surgical procedures have certain limitations.…”
mentioning
confidence: 99%